#### Answer

x = 1.142857143

#### Work Step by Step

Simplifying
3x + -7 + 17(1 + -1x) = -6
3x + -7 + (1 * 17 + -1x * 17) = -6
3x + -7 + (17 + -17x) = -6
Reorder the terms:
-7 + 17 + 3x + -17x = -6
Combine like terms: -7 + 17 = 10
10 + 3x + -17x = -6
Combine like terms: 3x + -17x = -14x
10 + -14x = -6
Solving
10 + -14x = -6
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-10' to each side of the equation.
10 + -10 + -14x = -6 + -10
Combine like terms: 10 + -10 = 0
0 + -14x = -6 + -10
-14x = -6 + -10
Combine like terms: -6 + -10 = -16
-14x = -16
Divide each side by '-14'.
x = 1.142857143
Simplifying
x = 1.142857143